ALAT PENGERING MASE PADA INDUSTRI RUMAHAN KERAMIK DINOYO MALANG: A MASE DRYER - indrawan nugrahanto; Sungkono Sungkono; Eka Mandayatma (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
At this time, the development of ceramic souvenirs is increasing in line with the increasing interest of domestic and foreign tourists, this technology seems to be required to be applied to the tools for supporting the production of ceramics which require more time efficiency in order to create a production process that balances the market. The ceramic mass dryer is the latest solution in the field of production, especially for drying the mass that has just come out of the mold. This dryer has a drying rate of up to 3 times faster than conventional outdoors dryers, but this dryer requires a power source to run it, the PID control contained in the system and the user friendly UI makes it easy for industrial entrepreneurs to facilitate the production. Ceramic mass dryer is a very useful long term solution, very flexible, and can function up to 5 years in the future. The ceramic mass dryer has other features such as automatic or manual mode selection and a timer that affects the drying speed of a ceramic mass object. The ceramic mass dryer is a drying machine for a ceramic object mass that uses a dimmer-controlled heater actuator to regulate the heat in drying process. This tool is an innovation in a ceramic mass object. this tool is also quite easy to run through the LCD UI and buttons on the display.